Electromagnetic Radiation Generated by Acoustic Excitation of Rock Samples - Yavorovich, Ludmila Vasilievna; Bespalko (Bespal'ko), Anatoly Alekseevich; Fedotov, Pavel Ivanovich; Baksht, Rina Borisovna (Томский политехнический университет, 2016)
The paper presents an experiment on acoustic excitation of electromagnetic radiation (EMR) signals in skarn, sandstone, and magnetite ore samples. For the skarn and sandstone samples, the EMR signal amplitude was observed to decrease with increasing ultimate strength. Supposedly, this effect can be explained by assuming that EMR is generated when an acoustic wave propagates through an electrical double layer. The presence of piezoelectric inclusions (e.g., quartz) in the magnetite ore enhances the analog EMR signal and its spectral components.
Keywords: акустическое возбуждение; горные породы; электромагнитное излучение; скарновые образования; магнитные руды; песчаники; rocks; electromagnetic radiation; skarn; magnetite ore; sandstone; artificial acoustic excitation